EZH2 overexpression in head and neck cancer is related to lymph node metastasis. (22nd January 2018) - Nienstedt, Julie C.; Schroeder, Cornelia; Clauditz, Till; Simon, Ronald; Sauter, Guido; Muenscher, Adrian; Blessmann, Marco; Hanken, Henning; Pflug, Christina
Abstract : Background: Enhancer of zeste homolog 2 (EZH2), the catalytic subunit of the polycomb repressive complex 2, plays an important role in tumor development and progression by interacting with histone and non‐histone proteins. EZH2 represents a putative therapeutic target and has been suggested as a prognostic marker in several cancer types. Material and Methods: This study investigates the prognostic relevance of immunohistochemical EZH2 expression in head and neck squamous cell carcinoma. Tissue microarray sections with 667 cancers of oral cavity, oro‐ and hypopharynx and larynx were analyzed for EZH2 expression. Results: Nuclear EZH2 staining was recorded in 322 (81.8%) of 394 cases. Staining was weak in 33 (10.2%), moderate in 128 (39.6%), and strong in 103 (32.0%) cancers. The prevalence of EZH2 expression in tumors of the oral cavity and the orohypopharynx was higher as compared to cancers of the larynx ( P = .0023). EZH2 expression was correlated to presence of lymph node metastasis ( P = .0089) but was unrelated to histological grade, tumor stage, surgical margin, or distant metastasis. EZH2 expression had no impact on patient survival. Conclusion: The high prevalence of EZH2 expression in head and neck squamous cell carcinoma stresses its capability as a therapeutic target.